MARKET RATIO ANALYSIS TO ASSESS FINANCIAL CONDITION AT PT. HM SAMPOERNA, Tbk. - Amru Usman; Annisa Karim Sinaga; Ade Ratna Dewi; Irhamah (PT. Radja Intercontinental Publishing, 2024)
This research was conducted with the aim of knowing how the financial performance of a company with financial analysis. Company with financial analysis. PT H.M Sampoerna Tbk has an efficient and healthy financial performance so as to increase the company's profits and achievements. Efficient and healthy so that it can increase profits and company performance. Analysis that analysis conducted at PT H.M Sampoerna includes liquidity ratios, solvency ratios, profitability ratios and activity ratios. Activity ratio. The results of this study are based on liquidity ratios proxied by Current Ratio and Quick Ratio. Quick Ratio, the company's financial performance conditions are not good. Profitability ratios proxied by Net Profit Margin, Return on Assets, and Return on Equity the company's financial performance conditions are good. Solvency ratios proxied by Debt to Total Assets Ratio and Debt to Total Equity Ratio are in good condition. the company's financial performance is good.